Job Design And Transformational Leadership In Enhancing Employee Performance At The Population And Civil Registration Office Of Surabaya City Through Work Motivation - Nurul Hidayah; Tri Kartika Pertiwi; Hesty Prima Rini (UNIVED Press, 2025)
This research aims to understand the role of Job Design and Transformational Leadership on the performance of employees at the Population and Civil Registration Office of Surabaya, with work motivation as a mediating factor. The number of respondents was 147 employees directly related to the performance of the office, selected through random sampling for the measurement of Job Design, Transformational Leadership, and Work Motivation, while employee performance was measured based on evaluations from their leaders. The analysis used SEM-PLS. This study proves that Job Design and Transformational Leadership have a direct and indirect effect on performance through work motivation, with an R-square value of 0.48 or 48%. However, work motivation has a low mediating value, with Upsilon values of 0.010495 and 0.010837. To enhance Job Design, it is essential to clarify task identity and objectives; leadership at the Surabaya Civil Registration Office should foster intellectual stimulation to motivate employees; organizations must fully support employee potential development.